AB0489 BETA 2 MICROGLOBULIN AS A PROGNOSTIC FACTOR IN CRYOGLOBULINEMIA NON ASSOCIATED WITH HEPATOTROPIC VIRUSES. (2nd June 2020) - Jeria, S.; Franco, T.; Baucells, A.; García-Guillén, A.; Lobo Prat, D.; Sainz Comas, L.; Park, H.; Millán Arciniegas, A. M.; Moya, P.; Mariscal, A.; Alserawan, L.; Laiz, A.; et al.
Abstract : Background: Cryoglobulinemia (CG) is a rare phenomenon related to haematological disorders, infections and autoimmune diseases. Age and renal involvement are known prognostic markers. Objectives: To describe the differential clinical features and the prognostic factors in a cohort of patients diagnosed with CG non-associated with hepatotropic viruses. Methods: A descriptive, retrospective study of a cohort comprised of 252 cryoglobulin positive samples, obtained from the immunology laboratory database of a tertiary hospital attending 450, 000 people over 1 year. 186 patients with CG positive samples were included, 87 of which were not associated with neither hepatitis B nor C virus. Demographic, clinical, serological and pathological data were collected. Nonparametric variables were compared using a Wilcoxon test. Results: Out of 186 reviewed patients, 87 (46.7%) are included in this study. The mean age at CG diagnosis was 60 (± 16) years. Mixed CG was the predominant subtype, detected in 66 (75.9%) patients, 10 of which (11.5%) were associated with glomerulonephritis (GN) with compatible biopsy, 17 (19.5%) with peripheral neuropathy (PN), 29 (33.3%) with non-erosive arthritis and 10 (11.5%) with leukocytoclastic vasculitis confirmed by skin biopsy. The clinical, epidemiological and serological characteristics of the sample are summarized in Table 1 . In the comparative analysis of patients with CG and Beta 2 microglobulin (β2M), CG and rheumatoid factor (RF), those with high β2M (>1.8 mg / L) presented significantly more GN (p0.016) and PN (p0.013). However, the association of RF with either GN (p0.948) or PN (p0.645) was not significant. Also, high β2M was significantly related to complement consumption of C4 (p: 0.015) but not of C3 (p: 0.063). In the 30 (34.5%) patients with skin manifestations, high β2M showed no statistically significant association. The main systemic autoimmune diseases associated were primary Sjögren's Syndrome (pSS) 37 (42.5%), Systemic Lupus Erythematosus (SLE) 9 (10.3%) and Systemic Sclerosis (SSc) 7 (8.05%). Conclusion: A direct association between presence of elevated levels of β2M and the existence of progression to glomerulonephritis and peripheral neuropathy is found in our cohort. No correlation is found between the presence of CG and other serological markers of autoimmunity except low C4. CG with elevated β2M does not associate with greater skin involvement or arthritis. References: [1]A.C. Desbois et al. Cryoglobulinemia: An update in 2019. Joint Bone Spine (2019) [2]Cacoub P, Cryoglobulinemia Vasculitis, The American Journal of Medicine (2015) Disclosure of Interests: None declared